2020
DOI: 10.1017/s0007114520004092
|View full text |Cite
|
Sign up to set email alerts
|

Low-carbohydrate diet and maternal glucose metabolism in Chinese pregnant women

Abstract: Few studies have suggested that long-term adherence to low-carbohydrate diets (LCD) may affect maternal glucose metabolism in western countries. We aimed to investigate the association between LCD during pregnancy and glucose metabolism in Chinese population. A total of 1,018 women in mid-pregnancy were recruited in 2017-2018. Participants underwent a 75g oral glucose tolerance test (OGTT). Daily dietary intakes over the past month were accessed using a validated food frequency questionnaire. The overall, anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 49 publications
(66 reference statements)
2
12
0
Order By: Relevance
“…Moreover, similar to the case presented here, a very-low-carbohydrate meal (6.7% carbohydrate, <10 grams) immediately prior to OGTT has been shown to alter OGTT results during pregnancy [ 11 ]. Recent data also suggest that low-carbohydrate diets are associated with positive 1-hour OGTT and diagnosis of gestational diabetes in pregnancy diabetes screening programs [ 12 , 13 ]. As gestational diabetes diagnosis is increasing, some of the obstetrics community recognizes the flawed nature of OGTT and posits that alternative screening tools will eventually replace the OGTT for detection of gestational diabetes [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, similar to the case presented here, a very-low-carbohydrate meal (6.7% carbohydrate, <10 grams) immediately prior to OGTT has been shown to alter OGTT results during pregnancy [ 11 ]. Recent data also suggest that low-carbohydrate diets are associated with positive 1-hour OGTT and diagnosis of gestational diabetes in pregnancy diabetes screening programs [ 12 , 13 ]. As gestational diabetes diagnosis is increasing, some of the obstetrics community recognizes the flawed nature of OGTT and posits that alternative screening tools will eventually replace the OGTT for detection of gestational diabetes [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…This was supported by other studies showing that a higher GDM risk was correlated with a higher consumption of animal fat (14) and animal protein (16) . In addition, a recent observational study from China indicated that the animal LCD score was positively associated with OGTT 1-h glucose (29) , suggesting that a low-carbohydrate dietary pattern with high animal fat Accepted manuscript and protein was associated with an increased risk of abnormal maternal glucose metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…This was supported by other studies showing that a higher GDM risk was correlated with a higher consumption of animal fat (14) and animal protein (16) . In addition, a recent observational study from China indicated that the animal LCD score was positively associated with oral glucose tolerance test 1-h glucose (29) , suggesting that a low-carbohydrate dietary pattern with high animal fat and protein was associated with an increased risk of abnormal maternal glucose metabolism. However, the positive association between the animal LCD score and GDM risk was observed to be non-linear in our study because the RR was higher in the third quartile than in the highest quartile of animal LCD score.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations